2021
DOI: 10.3390/ani11071875
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water with Saccharin Sodium Alters the Microbiota-Gut-Hypothalamus Axis in Guinea Pig

Abstract: The effects of saccharin, as a type of sweetener additive, on the metabolism and development of mammals are still controversial. Our previous research revealed that saccharin sodium (SS) promoted the feed intake and growth of guinea pigs. In this experiment, we used the guinea pig model to study the physiological effect of SS in the microbiota–gut–hypothalamus axis. Adding 1.5 mM SS to drinking water increased the serum level of glucose, followed by the improvement in the morphology and barrier function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Furthermore, our findings indicated that the RA and SS groups exhibited significantly higher serum levels of GHRP and the TGS group had an increased serum levels of CCK in comparison with the CN group. Consistent with our previous reports, dietary supplementation with 1.5 mM SS in drinking water initiated sweet receptor signaling within the gastrointestinal tract and altered the secretion of GHRP hormones 17 . Growth hormone‐releasing peptide, a brain‐gut peptide responsible for stimulating appetite, is known for its role in increasing gastric acid production, as well as promoting gastric motility and emptying 32 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, our findings indicated that the RA and SS groups exhibited significantly higher serum levels of GHRP and the TGS group had an increased serum levels of CCK in comparison with the CN group. Consistent with our previous reports, dietary supplementation with 1.5 mM SS in drinking water initiated sweet receptor signaling within the gastrointestinal tract and altered the secretion of GHRP hormones 17 . Growth hormone‐releasing peptide, a brain‐gut peptide responsible for stimulating appetite, is known for its role in increasing gastric acid production, as well as promoting gastric motility and emptying 32 .…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with our previous reports, dietary supplementation with 1.5 mM SS in drinking water initiated sweet receptor signaling within the gastrointestinal tract and altered the secretion of GHRP hormones. 17 Growth hormone-releasing peptide, a brain-gut peptide responsible for stimulating appetite, is known for its role in increasing gastric acid production, as well as promoting gastric motility and emptying. 32 The hypothalamus functions as a central brain structure that processes information regarding overall energy levels and metabolic status through hormones or nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that Ileibacterium -valens was significantly increased in the gut microbiota of mice in the LF intervention group compared to the control group. The study [33] had confirmed that abundance of Erysipelotrichaceae-Ileibacterium was associated with obesity. It may affect the host metabolism and inflammatory diseases and is closely related to obesity [34].…”
Section: Discussionmentioning
confidence: 77%